Is higher resolution always better? A comparison of open-access DEMs for optimized slope unit delineation and regional landslide prediction - M. Ahmed; G. Titti; S. Trevisani; L. Borgatti; M. Francioni (Natural Hazards and Earth System Sciences)
Digital elevation models (DEMs) play a key role in slope instability studies, ranging from landslide detection and recognition to landslide prediction. DEMs assist these investigations by reproducing landscape morphological features and deriving relevant predisposing factors, such as slope gradient, roughness, aspect, and curvature. Additionally, DEMs are useful for delineating map units with homogeneous morphological characteristics, such as slope units (SUs).